2002
DOI: 10.1103/physreva.65.054502
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant corrections to the1s2stwo-photon resonance for the hydrogen atom

Abstract: The nonresonant (NR) corrections are estimated for the most accurately measured two-photon transition 1s-2s in the hydrogen atom. These corrections depend on the measurement process and set a limit for the accuracy of atomic frequency measurements. With the measurement process adopted in the modern experiments the NR contribution for 1s-2s transition energy can reach 10 −3 Hz while the experimental inaccuracy is quoted to be ± 46 Hz. PACS numbers: 31.30.Jv, 12.20.Ds, 0620Jr., 31.15.-p Nonresonant (NR) correcti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Then, later, in [12,13], the importance of nonresonant corrections for the Lamb shift measurements and the process of radiative electron capture in highly charged hydrogen-like ions was demonstrated. In further NR corrections were evaluated for the hydrogen atom in [14][15][16][17][18], whereas the most essential NR contribution was found in [19]. It is the nonresonant correction including the fine structure splitting of atomic levels [16,19] represents a special interest in further investigations, see, for example, [20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Then, later, in [12,13], the importance of nonresonant corrections for the Lamb shift measurements and the process of radiative electron capture in highly charged hydrogen-like ions was demonstrated. In further NR corrections were evaluated for the hydrogen atom in [14][15][16][17][18], whereas the most essential NR contribution was found in [19]. It is the nonresonant correction including the fine structure splitting of atomic levels [16,19] represents a special interest in further investigations, see, for example, [20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…In further NR corrections were evaluated for the hydrogen atom in [14][15][16][17][18], whereas the most essential NR contribution was found in [19]. It is the nonresonant correction including the fine structure splitting of atomic levels [16,19] represents a special interest in further investigations, see, for example, [20][21][22][23][24][25][26]. Recently a theoretical analysis of the experiment [5] was presented in [27], where it was shown that QIE effects should be carefully studied with each specific spectroscopic measurement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in Ref. [7], the authors explain in the text after Eq. ( 2) that "the velocity [gauge] form follows originally from the [fully relativistic] QED description" and should therefore be used off resonance, for the obvious reason that the nonrelativistic limit of the Dirac matrix vector α, which enters the relativistic expression for the self-energy [17] is the momentum operator p/(mc).…”
mentioning
confidence: 99%
“…( 12) we have to take into account all neighboring terms in the sum over n. Then in case of only two neighboring states, only terms in Eq. ( 12) with n = a (leading resonant term to which we introduce NR correction) and n = b (closest by energy to the resonant term) need to be considered [19][20][21][22][23].…”
Section: Qed Theory Of Resonant Two-photon Scattering On Atomic Electronmentioning
confidence: 99%